HOW PREVIOUS-YEAR BUSINESS STRATEGY SHAPES FIRMS' SUBSEQUENT CSR PERFORMANCE - Kholifah, Siti Nur; Naimah, Zahroh (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study examines how previous-year business strategy shapes firms' corporate social responsibility performance in an emerging market such as Indonesia. Building on the RBV, we argue that a strategic orientation in the prior period configures resources and capabilities that materialise in CSR activities, disclosures, and scores. Using data from Indonesian firms listed on the Indonesia Stock Exchange from 2018 to 2023, business strategy is classified according to the Miles and Snow (1978) typology and operationalised using Bentley et al.'s (2013) six-ratio measure, collapsed into an analyser–defender dummy, and lagged by 1 period. CSR performance is captured using a GRI-based disclosure score. Baseline regressions show that lagged business strategy is positively associated with CSR performance, and this relationship remains robust when year fixed effects are included. However, it weakens once sector fixed effects are introduced. A split-sample analysis shows that the effect of lagged business strategy is strong and significant only for non–Scope 1 disclosers and largely vanishes for Scope 1 disclosers, where external pressures are higher. Overall, the findings suggest that prior-year business strategy functions as an important upstream driver of CSR. Still, its impact is contingent on institutional and disclosure environments, particularly the degree of carbon transparency.